A Pharmacometric Method for Quantitative Determination of Improvement in Body Composition and Characterization of the Exposure-Response Relationship during Treatment of Obesity with Tirzepatide - Chigutsa, Emmanuel; Her, Lucy; Ma, Xiaosu; Urva, Shweta; Schneck, Karen (Clinical pharmacology and therapeutics, 2025)
About half of the world's population is living with overweight or obesity. Tirzepatide is an approved treatment for chronic weight management. We sought to characterize the exposure-response relationship for weight reduction in patients with overweight or obesity and quantify the associated changes in body composition. Monthly body weight measurements were available from 2,539 study participants in a phase 3 clinical trial investigating placebo, 5, 10, or 15 mg of tirzepatide administered once-weekly. The dependent variables used for modeling were fat-free mass (FFM) and fat mass. These FFM and fat mass values were calculated for each patient based on their total body weight, height, and sex. The exposure-response model revealed that administration of tirzepatide resulted in three times greater reduction of fat mass than that of FFM. This differential effect resulted in improved body composition over time. The model results showed good agreement with available data from a subset (10%) of clinical trial participants who had dual energy x-ray absorptiometry (DXA) measurements. For the same drug exposure, females achieved greater weight reduction than males. Study participants with higher baseline weight or body mass index at baseline had a slower rate of weight reduction and were expected to take longer to reach their nadir weight. We present and propose the use of a pharmacometric-based body composition model to describe weight reduction in future clinical trials investigating similar drugs in similar patient populations, in lieu of DXA scans. In such future trials, our approach can be used to describe exposure-response relationships, optimize doses, and investigate covariates, while considering potential differences in fat mass and FFM.